2016
DOI: 10.1007/s10555-016-9617-1
|View full text |Cite
|
Sign up to set email alerts
|

miR clusters target cellular functional complexes by defining their degree of regulatory freedom

Abstract: Using the two paralog miR-23∼27∼24 clusters as an example and combining experimental and clinical data in a systematical approach to microRNA (miR) function and dysregulation, a complex picture of their roles in cancer is drawn. Various findings appear to be contradictory to a larger extent and cannot be fully explained by the classical regulatory network models and feedback loops that are mainly considered by one-to-one regulatory interactions of the involved molecules. Here, we propose an extended model of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 165 publications
3
17
0
Order By: Relevance
“…These different observations of dysregulated miR has also been observed in other context for which the authors provided the model of regulators freedom for miR regulation (see review in ref. [8]).…”
Section: Clinical Relevance Of Mir In Cafmentioning
confidence: 99%
See 1 more Smart Citation
“…These different observations of dysregulated miR has also been observed in other context for which the authors provided the model of regulators freedom for miR regulation (see review in ref. [8]).…”
Section: Clinical Relevance Of Mir In Cafmentioning
confidence: 99%
“…They have to be differentiated from miR families where sequence homology is the major determinant. Clustering appears to be an important way of evolutionary spreading of miR genes throughout the human genome and many clusters have a significant degree of evolutionary conservation [7], indicating that miR clustering is important for their biological role due to combined regulation of their expression [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Members of miR-23/24/27 have been proposed to have important roles in angiogenesis (5–8). In addition, deregulated expression of these miRNAs and cancer-related roles have been described in many studies with varying results (9). miR-23 and miR-27 are shown to facilitate EMT in several types of cancer including lung cancer (9).…”
mentioning
confidence: 99%
“…In addition, deregulated expression of these miRNAs and cancer-related roles have been described in many studies with varying results (9). miR-23 and miR-27 are shown to facilitate EMT in several types of cancer including lung cancer (9). We also previously reported that TGF-β induces the expression of miR-23a in A549 lung cancer cells (10).…”
mentioning
confidence: 99%
“…Clustering appears to be an important way of evolutionary spreading of miR genes throughout the human genome and many clusters have a significant degree of evolutionary conservation [7], indicating that miR clustering is important for their biological role due to combined regulation of their expression. [8] The aim of this review was to summarize the current understanding on a) how miRs are involved in cancer cell -tumor environment/stroma communication, specifically the transformation of NFs into CAFs, their involved targets and signaling pathways in these interactions; and b) whether CAFrelated miR expression profiles are clinically relevant. By reviewing the literature we also found evidence that miRs have very similar roles in the activation of hepatic (HSC) and pancreatic stellate cells (PSC) which are also specifically activated fibroblasts being part of precancerous fibrotic diseases, like pancreatic and hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 99%